Fenestrated and covered frozen elephant trunk technique for management of chronic aortic dissection. Issue 12 (28th September 2022) - Okamura, Homare; Kitada, Yuichiro; Wada, Yohnosuke; Adachi, Hideo
Abstract: Background: Reintervention for residual dissection after repaired type A aortic dissection remains challenging. When a frozen elephant trunk (FET) is used, the incidence of distal stent graft‐induced new entry (d‐SINE) is reportedly high in chronic dissection. Aims: We report a case of successful redo arch repair using fenestrated and covered FET techniques for chronic residual aortic dissection. Methods: After the arch was transected proximal to the left subclavian artery (LSCA), and a modified FET prosthesis, in which the distal edge of the FET was covered, was deployed. A fenestration was created in the FET on the LSCA aspect. Results: The postoperative course was uneventful. Discussion: The distal edge of the FET was covered to prevent d‐SINE. Creation of a fenestration on the FET eliminates the need to reconstruct the LSCA. Conclusion: The fenestrated FET technique simplifies redo arch repair and the covered FET technique can potentially prevent d‐SINE.